2020
DOI: 10.3389/fphys.2020.00083
|View full text |Cite
|
Sign up to set email alerts
|

Polyunsaturated Fatty Acid Composition of Cerebrospinal Fluid Fractions Shows Their Contribution to Cognitive Resilience of a Pre-symptomatic Alzheimer’s Disease Cohort

Abstract: Alzheimer's disease (AD) pathology is characterized by an early and prolonged decrease in the amyloid peptide (Aβ) levels concomitant with a later increase in phosphotau concentrations in cerebrospinal fluid (CSF). We propose that changes in lipid metabolism can contribute to the abnormal processing of Aβ 42 in AD. Our aim was to determine if polyunsaturated fatty acid (PUFA) metabolism can differentiate presymptomatic AD from normal aging and symptomatic AD. Using neuropsychology measures and Aβ 42 /T-tau in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 79 publications
1
23
0
Order By: Relevance
“…30–200 nm-sized particles that we described in CSF to have neurotransmitters, lipids, active enzymes, and signaling functions and are likely derived from brain cells via exocytosis and vesicle signaling ( Harrington et al, 2009 ). We also reported that these nanoparticles are rich in the GP class of lipids, with compartmentalization between the SF and NP fractions of CSF ( Fonteh et al, 2013 , 2015 , 2020 ). Here, we provide evidence to support this hypothesis by finding that GPs and SPs in both SF and NP fractions are higher in CH-PATs and lower in dementia.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…30–200 nm-sized particles that we described in CSF to have neurotransmitters, lipids, active enzymes, and signaling functions and are likely derived from brain cells via exocytosis and vesicle signaling ( Harrington et al, 2009 ). We also reported that these nanoparticles are rich in the GP class of lipids, with compartmentalization between the SF and NP fractions of CSF ( Fonteh et al, 2013 , 2015 , 2020 ). Here, we provide evidence to support this hypothesis by finding that GPs and SPs in both SF and NP fractions are higher in CH-PATs and lower in dementia.…”
Section: Discussionmentioning
confidence: 82%
“…Neither medications nor measured blood lipids differ between the CH-NAT, CH-PAT, and AD groups ( Harrington et al, 2013 ; Chew et al, 2020 ). The comprehensive dietary questionnaire was only analyzed with confidence in the CH sub-groups to avoid any bias from impaired memories in those with dementia; the dietary lipid intake did not differ between CH-NAT and CH-NAT participants ( Fonteh et al, 2020 ). These results suggest that the changes mentioned above in GPs and SPs in biochemical and dementia stages likely result from the brain pathophysiology.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…AA increased in brains, erythrocytes, and CSF of AD individuals (Thomas et al, 2016;Goozee et al, 2017;Fonteh et al, 2020). LA decreased in AD brain and plasma (Snowden et al, 2017;Cunnane et al, 2012).…”
Section: Fatty Acidsmentioning
confidence: 92%
“…DHA decreased in brains, circulation, and CSF of AD individuals (Fonteh et al, 2014(Fonteh et al, , 2020de Wilde et al, 2017;Snowden et al, 2017;Hosseini et al, 2020). EPA decreased in brain and circulation of AD individuals (Hosseini et al, 2020).…”
Section: Fatty Acidsmentioning
confidence: 96%